Physical activity, TV viewing, and human development index in Brazilian adolescents: Results from the National School Health Survey - Raphael Henrique de Oliveira Araujo; Danilo Rodrigues Pereira da Silva; Thayse Natacha Queiroz Ferreira Gomes; Ricardo Aurélio Carvalho Sampaio; Antônio Evaldo dos Santos; Roberto Jerônimo dos Santos Silva (Universidade Estadual Paulista (UNESP), 2021)
Abstract Aim: This study aimed to examine the association between physical activity (PA) indicators and TV viewing as a function of the Human Development Index (HDI). Method: This cross-sectional study was based on data from the National School Health Survey, which was composed of 102,072 students (14.28±1.03; 51.3% girls). Total PA, active commuting to school (ACS) and TV viewing were assessed by questionnaires and classified through a gradual scale ranging from "F" (low) to "A+" (high). The correlation between total PA, ACS, TV viewing and HDI was verified by Spearman's Correlation and presented in rs. Results: HDI was positively associated with total PA [girls: rs = 0.572 (p < 0.001); boys: rs = 0.843 (p < 0.001)] and ACS [girls: rs = 0.433 (p < 0.001); boys: rs = 0.554 (p < 0.001)]; while a negative correlation was found between HDI and TV viewing [girls: rs = -0.330 (p < 0.001); boys: rs = -0.348 (p < 0.001)]. Conclusions: Brazilian adolescents from states with higher HDI were more active and spent more time watching TV than their counterparts from states with lower HDI.